Gender Gap in the Economic Sector in Siding District, Bengkayang Regency - Sigit Sapto Wibowo; Yusuf; Shendy Morgen Ichuan Delodo; Dwita Suci Rochima (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2026)
Gender inequality in women's economic activities remains a critical issue in rural and border regions, shaped by both household dynamics and structural conditions. This study aims to analyze gender disparities in the economic sector by comparing the experiences of women in Upper Siding (Sungkung 1, Sungkung 2, and Sungkung 3) and Lower Siding (Hli Buei, Tamong, and Siding) villages in Siding District, Bengkayang Regency, Indonesia. A comparative qualitative approach employing the Harvard Analytical Framework was used, involving 150 female respondents selected through purposive sampling. Data were collected through in-depth interviews, field observations, questionnaires, and a review of relevant literature. The findings reveal that women in both regions perform dual roles; however, women in Upper Siding experience a significantly heavier workload due to geographical constraints, limited infrastructure, and restricted mobility. Access to business capital among women in Upper Siding ranges from only 15% to 23%, considerably lower than that of women in Lower Siding, which ranges from 52% to 77%. Furthermore, women in Lower Siding demonstrate greater participation in household economic decision-making. These findings suggest that gender inequality is influenced not only by intra-household relations but also by structural factors, including geography, accessibility, infrastructure, and local social norms. This study contributes to the growing body of literature on gender and rural economies, particularly in remote, border, and underdeveloped regions.